Reflectivity and microhardness of sulfide minerals as genetic information source (case study: pyrite and arsenopyrite) - Sinkina, Ekaterina Andreevna; Korovkin, M.V.; Savinova, Olesya Vyacheslavovna; Makarova, A.A. (IOP Publishing, 2016)
Reflectivity and microhardness of pyrite and arsenopyrite of black shale gold-ore deposits in Chertovo Koryto (Patom upland) were studied. It was found that sulfides of different generations are characterized by different values of above-mentioned parameters which is associated mechanical and isomorphic impurities.
Keywords: микротвердость; сульфидные материалы; пириты; черные сланцы; рудные минералы; отражательная способность